1969
DOI: 10.1037/h0027380
|View full text |Cite
|
Sign up to set email alerts
|

"Test-wiseness" on personality scales.

Abstract: Test-wiseness on self-report personality scales was explored, using measures of accuracy in estimating the frequency of endorsement of personality items, estimating their social desirability, and identifying and "keying" items that measured the same factor, as well as indices of ability to change scores on standard personality scales when they were administered with "fake-good" and "fake-bad" instructions. 'I'hes e variables generally did not correlate with each other, and they had only moderate and scattered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1971
1971
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…They might have high self-efficacy and believe that their high mental abilities will likely be sufficient to secure a high test score (De Fruyt, Aluja, Garcia, Rolland, & Jung, 2006). In this type of situation, willingness plays a much more important role because high mental ability applicants are capable of faking and probably could recognize the opportunity to fake (as demonstrated in experimental studies ;Furnham, 1986;Kimber, 1947;Lao, 2001;Noll, 1951;Stricker, 1969).…”
Section: Understanding the Components Of Faking Likelihoodmentioning
confidence: 94%
See 1 more Smart Citation
“…They might have high self-efficacy and believe that their high mental abilities will likely be sufficient to secure a high test score (De Fruyt, Aluja, Garcia, Rolland, & Jung, 2006). In this type of situation, willingness plays a much more important role because high mental ability applicants are capable of faking and probably could recognize the opportunity to fake (as demonstrated in experimental studies ;Furnham, 1986;Kimber, 1947;Lao, 2001;Noll, 1951;Stricker, 1969).…”
Section: Understanding the Components Of Faking Likelihoodmentioning
confidence: 94%
“…For example, studies that have used experimental designs and instructed participants to take personality measures under different instructions (e.g., fake good, fake bad, respond honestly) have shown that individuals who are higher in mental abilities have higher ability to fake and respond to personality questions with more distortion (Bing, Whanger, Davison, & VanHook, 2004;Furnham, 1986;Grubb & McDaniel, 2007;Kimber, 1947;Lao, 2001;Noll, 1951;Stricker, 1969). Thus, these researchers argue that faking is a function of the respondent's mental abilities.…”
Section: Introductionmentioning
confidence: 93%
“…In principle TW can still operate in other measurements, for example personality measurements (Strieker 1969; see also Guilford 1954). The only thing that in the definition of TW possibly links TW with achievement and ability tests is the expression '... to receive a high score in relation to the purpose of the test'.…”
Section: Analysis Of Test-wisenessmentioning
confidence: 97%
“…As seen above, TW includes not only the ability to use faults in the formats of the tests, but also the ability to pay attention to the purpose of the test and the ability to use characteristics outside the test itself. The few studies that have been carried out with the aim of empirically rooting TW have also shown that different abilities are probably included under the designation TW (Diamond & Evans 1972, Strieker 1969.…”
Section: Analysis Of Test-wisenessmentioning
confidence: 98%
See 1 more Smart Citation